Perbedaan Jumlah Limfosit dan Monosit serta Morfologi Eritrosit pada Perokok Tembakau dan Elektrik sebagai Faktor Risiko Aterosklerosis pada Remaja - Laila Nisa, Isra; Rohmi; Khusuma, Ari; Zaetun, Siti (Journal of Indonesia Laboratory Students (JILTS), 2024)
Background : Smoking from adolescence can increase the risk of atherosclerosis because there is a buildup of fibrolipids and other substances in the blood that can cause plaque. Meanwhile, research results show that e-cigarettes are no less dangerous than tobacco cigarettes. Namely, the number of lymphocytes in e-smokers is 54% and tobacco smokers are 39% (Mega, 2020). The novelty of this research is to look at differences in erythrocyte count and morphology in adolescents at risk of atherosclerosis. Research Objectives : To determine the differences in the number of lymphocytes and monocytes and the morphology of erythrocytes in tobacco and electronic smokers as risk factors for atherosclerosis in adolescents. Research Methods : This research is an analytical observational study with a cross sectional research design and uses the lameshow formula to determine the sample size so that a sample size of 30 samples can be obtained. Data were tested using the Independent T-test and Mann Whitney-U test. The results of the study : The average percentage of lymphocytes and monocytes in tobacco and electronic smoker is 37% & 27% lymphocytes and 7% & 6% monocytes. From 15 samples of tobacco smokers the results were normal and from 15 samples of e-smokers there was 1 lymphocyte result below normal. Also, the abnormal cells found include anulocytes, tear drops, burr cells, ovalocytes and stomatocytes. Conclusion : There are differences in the number of lymphocytes and monocytes as well as erythrocyte morphology in tobacco and electronic smokers as risk factors for atherosclerosis in adolescents with the probability value for lymphocytes being 0.01<0.05 and monocytes 0.04<0.05.